2020
DOI: 10.1590/2175-7860202071003
|View full text |Cite
|
Sign up to set email alerts
|

Tree species richness and composition in a fragmented landscape of the Brazilian lowland Atlantic Forest

Abstract: Tropical forests are one of the most important ecosystems and loss of biological diversity in these is a major concern. We studied seven forest remnants on the coast of Rio de Janeiro, southeastern Brazil, three medium-sized (24-63 ha) and four small (5-11 ha), to assess the influence of size, degree of disturbance and isolation on composition and diversity of the tree layer. A total of 443 species in 60 families and 185 genera were recorded, with Myrtaceae, Lauraceae and Fabaceae being the most species-rich f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
2
0
1
Order By: Relevance
“…These results confirm studies of plant diversity of the Atlantic Forest covering the arboreal and non-arboreal strata, the herbs and lianas are responsible for about 50% of the total wealth found (Pessoa & Araujo, 2020).…”
Section: Resultssupporting
confidence: 86%
“…These results confirm studies of plant diversity of the Atlantic Forest covering the arboreal and non-arboreal strata, the herbs and lianas are responsible for about 50% of the total wealth found (Pessoa & Araujo, 2020).…”
Section: Resultssupporting
confidence: 86%
“…The observed results corroborate the species richness of Euphorbiaceae, Lauraceae, Leguminosae, Melastomataceae, Myrtaceae and Rubiaceae, families indicated among the most diverse in the Atlantic Forest and among the ten with the greatest richness among Angiosperms in Brazil (BFG 2015). The prominence presented by these families was also observed in studies of the structure and composition of different stretches of Atlantic Forest in the state of Rio de Janeiro (e.g., Kurtz & Araujo 2000, Barros 2008, Machado 2018, Pessoa & Araujo 2020 and in investigations of the flora of Área de Proteção Ambiental de Mangaratiba/Parque Estadual Cunhambebe (Maurenza et al 2018) and Área de Proteção Ambiental de Cairuçu (Marques et al 1997). The genera Eugenia and Myrcia, highlighted in this study, are also identified as the most diverse in the country (BFG 2015).…”
Section: Floristic Analysismentioning
confidence: 72%
“…Island environments have long instigated biogeographic investigations (e.g., MacArthur & Wilson 1967, Whittaker 1998. As islands vary in shape, size, spatial arrangement, geology, environments and biotic characteristics, investigations conducted on islands contribute to the understanding of fragmented continental landscapes (Tavares et al 2019;Pessoa & Araujo 2020), interpreted as habitat islands (Whittaker 1998). On the southern coast of Rio de Janeiro, especially between the municipalities of Mangaratiba and Paraty, studies carried out both in continental areas (Marques et al 1997, Maurenza et al 2018 and in islanders (e.g., Callado et al 2009) have shown relevance as sources of biological information, especially in relation to biodiversity conservation in fragmented areas (Carvalho et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A Zona da Mata de Minas Gerais, inserida na Mata Atlântica, também, apresenta reduzida cobertura florestal remanescente, em sua maioria, compondo mosaicos de fragmentos florestais em diferentes estágios de sucessão ecológica secundária KUNZ;MARTINS, 2014). A topografia acidentada da região, aliada às condições ambientais e isolamento desses fragmentos florestais, contribuem para mudanças na estrutura e regeneração natural da floresta secundária (FERREIRA et al, 2015;SANTOS et al, 2017;PESSOA;ARAÚJO, 2020). O acompanhamento dessas mudanças, nesses fragmentos, possibilita conhecer a estrutura atual da floresta remanescente e avaliar os impactos de ações antrópicas na conservação biológica de espécies (JOLY et al, 2014;MATOS et al, 2019;PIOTTO et al, 2019).…”
Section: Introdução Geralunclassified